Aplicación de una auditoría informática en la Cooperativa de Ahorro y Crédito “Virgen del Cisne”, ubicada en la parroquia Eloy Alfaro cantón Latacunga provincia Cotopaxi, al periodo 01 de enero al 31 de diciembre del 2013 - Araujo Tarco, Wilma Verónica (2015)
The development of this research is focused on the application of a computing auditing; it is important to make technological audits today. It plays a substantial role, because by applying such results in real and appropriate information for decision making, that allows the institution conduct its activities and stay competitive. The goal to this research is to evaluate the computer system by applying the methodology of Computing Audit under the support of the working papers it could be obtained relevant information to generate a report with practical and useful recommendations for decision-making of the senior management. It is precise establishing the execution of the research, as well as determinate the tools or strategies that allows to gather all the required information and eventually will be the implementation of Computing Auditing that allows make a review to the operation at the computer system of the Cooperative. The research is based on methods, techniques and tools that facilitate the collection of criteria, features, comments, documents and files that are used, this will allow them to measure, evaluate and collect data of the correct functioning in the system within the institution to determine the real status.